2014
DOI: 10.1111/head.12336
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Referral of Head Pain in Migraineurs: Effects on the Nociceptive Blink Reflex

Abstract: Objective.-To investigate cervical, interictal reproduction of usual head pain and its effect on the nociceptive blink reflex in migraineurs.Background.-Anatomical and neurophysiological studies in animals and humans have confirmed functional convergence of trigeminal and cervical afferent pathways. Migraineurs often present with occipital and neck symptoms, and cervical pain is referred to the head in most cases, suggesting that cervical afferent information may contribute to headache. Furthermore, the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
6

Year Published

2016
2016
2025
2025

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 88 publications
1
19
0
6
Order By: Relevance
“…24,104 This is reinforced by demonstrable alterations in neuronal excitability in the spinal cord secondary to ongoing peripheral nociception. 77,80,81,105 Furthermore, a recent study has demonstrated significant concomitant diminution of recognized central sensitization measures in association with improved cervical movement. 106 This finding strengthens the notion that chronic pain in cervical whiplash patients could be maintained by peripheral nociceptive input.…”
Section: Discussionmentioning
confidence: 99%
“…24,104 This is reinforced by demonstrable alterations in neuronal excitability in the spinal cord secondary to ongoing peripheral nociception. 77,80,81,105 Furthermore, a recent study has demonstrated significant concomitant diminution of recognized central sensitization measures in association with improved cervical movement. 106 This finding strengthens the notion that chronic pain in cervical whiplash patients could be maintained by peripheral nociceptive input.…”
Section: Discussionmentioning
confidence: 99%
“…С учетом конвергенции афферентных волокон тройничного нерва и 3 верхних шейных спинно-мозговых корешков на уровне 2 нейронов ядра спинномозгового пути и задних рогов верхних шейных сегментов спинного мозга связь головных и лицевых болей с патологией структур шеи являет-ся несомненной [17,21]. При этом Международная классификация расстройств, сопровож дающихся головной болью (3-я редакция (бета-версия), 2013 г.…”
Section: ключевые слова: цервикогенная головная больunclassified
“…Центральная сенситизация является одним из ос-новных механизмов поддержания хронической боли, при ее наличии утрачивается зависимость от периферических пус-ковых факторов, развивается резистентность к терапии [29]. По данным нейрофизиологических исследований, аффе-рентные импульсы при боли в шее вносят вклад в формиро-вание ГБ у пациентов с мигренью [30]. Снижение порога МР у наших пациентов свидетельст-вует о нарушении функционального состояния тригеми-нальных нейронов ствола, что подтверждает наличие цент-ральной сенситизации.…”
Section: с о с т о я н и е а н т и н о ц и ц е п т и в н о й с и с т unclassified
“…А снижение порога боли НФР ука-зывает на недостаточность супраспинальных антиноцицеп-тивных влияний и дисфункцию систем нисходящего конт-роля боли. Эти результаты подтверждают и другие авторы, которые показали у пациентов с мигренью нарушения про-ведения по тригеминальным и цервикальным афферент-ным путям [30].…”
Section: с о с т о я н и е а н т и н о ц и ц е п т и в н о й с и с т unclassified